Risk factors of upper gasterointestinal tract bleeding caused by stress ulcer - Abdul Latief; Alan Roland Tumbelaka; Rulina Suradi; WEnny Lazdya Taifur (Paediatrica Indonesiana, 1999)
During the period of December 1st 1997 until April 30th 1998, an observational study with cross sectional design was conducted at the Pediatric Intensive Care Unit (PICU). Risk factors of the occurrence of upper gastrointestinal tract bleeding (VGTB) on patients admitted to the PICU Medical School University of Indonesia/ Cipto Mangunkusumo Hospital were described analysed. Upper gastrointestinal tract bleeding was confirmed if there was evidence of brown or coffee ground material of the gastric fluid in the nasogastric or gastrotomy tube, hematemesis or melena, which was subsequently proved by benzidin test. Â The risk factors in this study was defined based on the risk factors found from previous studies i.e. shock, sepsis. severe head injury, multiple complication, liver insufficiency, pneumonia, respiratory failure, intervention during treatment (operation >3 hours, ventilator, corticosteroid >3 days). From 26 patients with UGTB risk factors in this study, 19 persons (73%) developed UGTB. The proportion of UGTS was not different on the patient's characteristic (age, sex, nutritional status). UGTB found were bleeding through nasogastric tube (58%) and occult bleeding 37%, hematemesis only one person (II %).The majority of VGTB occurred on the 3rd Â day of hospitalization (84%) and after ventilator usage of >48 hours (58%). Patient who underwent >3 hours operations were craniotomies. All the patients who received >3 days of corticosteroid (4 persons) developed VGTS.